(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The art of manuscripts or the art of the Qur’an is one of the important topics in the field of Islamic archaeology in general and decorative arts in particular, and it forms the main basis for studying the arts of the book. This study presents the aesthetics of calligraphic decorations, how they developed and the many aesthetics they carry, as it was a vast field to show the ingenuity of the Muslim artist, and that wealth that is treasured by manuscripts, especially the Noble Qur’an and archaeological scenes, because of the arts they contain in the field of calligraphy and decoration, which enriches archaeological studies through the diversity of Islamic decoration forms, the most important of which are vegetal, geometric and calligraphic decorations, and their forms used in a new artistic style.